Genetic Diversity of Flying Fish (Exocoetidae) in Southeast Sulawesi, Indonesia - Indrayani, Indrayani; Ambardini, Sri; Pariakan, Arman; Nur, Indriyani (Bogor Agricultural University, Indonesia, 2024)
Flying fish (Exocoetidae) is a pelagic fishery commodity that holds economic value among the people of eastern Indonesia. Flying fish are advantageous as they are abundant in Indonesian sea waters, making them an affordable source of omega-3, which is beneficial for human health. However, the high demand for flying fish has resulted in overfishing, which poses a risk of reducing their natural population. Proper management of this commodity is necessary to minimize these risks. Effective management requires adequate information, including genetic diversity data. This study aims to determine the genetic diversity of flying fish in Southeast Sulawesi, specifically in the Banda Sea and Bone Bay populations. Tissue samples were collected from flying fish in the two populations during the study in March 2022. The results show that the genetic diversity values of flying fish in Bone Bay and the Banda Sea were 0.984 and 1.00, respectively, while the nucleotide diversity values were 0.021 and 0.018. High genetic diversity values and nucleotide diversity values were found between the two populations, with values of 0.990 and 0.020, respectively. Based on phylogenetic analysis, the two populations in Southeast Sulawesi are genetically similar.